Muslims, Christians, and Jesus understanding the world of Islam and overcoming the fears that divide us - Medearis, Carl (Bethany House Publishers, 2017)
Provides new insights into the top questions people have about Muslims and Islam in this completely updated guide to understanding today's Muslim. With practical tips and fascinating stories, he shares culturally sensitive ways for Christians to get to know Muslims and shows how common ground is the best foundation for turning hearts to Jesus.